2013
DOI: 10.1089/tmj.2013.0034
|View full text |Cite
|
Sign up to set email alerts
|

Help Is in Your Pocket: The Potential Accuracy of Smartphone- and Laptop-Based Remotely Guided Resuscitative Telesonography

Abstract: UNEs can confidently be guided to obtain critical findings using simple information technology resources, based on the receiving/transmitting device found in most trauma surgeons' pocket or briefcase. Global US mentoring requires only Internet connectivity and initiative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 36 publications
1
55
0
Order By: Relevance
“…We previously showed that lung ultrasonography can be performed accurately with economical mobile equipment by nonphysicians who are guided remotely, 3,4 a paradigm largely started to support space medicine. 5 In addition to augmenting diagnosis, we also suggest that RTMUS might help ongoing screening at home for self-isolating adults at risk of or with selflimited COVID-19.…”
Section: Lung Ultrasonography In a Woman With Covid-19: This Examinatmentioning
confidence: 99%
“…We previously showed that lung ultrasonography can be performed accurately with economical mobile equipment by nonphysicians who are guided remotely, 3,4 a paradigm largely started to support space medicine. 5 In addition to augmenting diagnosis, we also suggest that RTMUS might help ongoing screening at home for self-isolating adults at risk of or with selflimited COVID-19.…”
Section: Lung Ultrasonography In a Woman With Covid-19: This Examinatmentioning
confidence: 99%
“…Several studies have investigated the use of telesonography, in which ultrasound images are transferred to a remote display in real time to remedy a lack of on-site expert interpreters in under-resourced settings [3][4][5][6][7][8][9][10][11][12][13][14][15]. The term Btelesonographyŵ as first used in 1992 by Mendlowitz [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the process of analog-to-digital conversion, the data must be compressed, and thus, the resolution of both video and still images is degraded. Today, although images remain digital during every step of image transmission, systems that transmit compressed data at a degraded resolution have been actively investigated because the available bandwidth is often limited [4][5][6][7][8][9][10][11][12][13]. These studies have demonstrated that the perception of the image quality is not significantly affected by the degraded resolution because the resolution required for the perception of image quality and smoothness is low [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation